Au‐Nanoparticle‐Array/Aligned‐Ag‐Nanowire‐Based Flexible Dual Plasmonic Substrate for Sensitive Surface‐Enhanced Raman Scattering Detection. (31st October 2021) - Tang, Zilun; Wu, Jianyu; Liu, Xiaochun; Su, Qiuping; Yin, Xingshan; Huang, Zhiyi; Lin, Xiaofeng; Lin, Wenjing; Yi, Guobin
Abstract: The fabrication of flexible surface‐enhanced Raman scattering (SERS) substrates for sensitive detection on uneven or irregular surfaces is challenging. In this study, a flexible dual plasmonic SERS (FDPS) substrate rationally constructed using Au nanoparticle (AuNP) arrays/aligned Ag nanowires (AgNWs) and elastic polyurethane (PU) is demonstrated. It exhibits high sensitivity (detection limit of 10 −8 m for melamine and 10 −10 m for malachite green) and excellent reproducibility. The well‐designed structure of AuNP arrays/aligned AgNWs fabricated using block copolymer self‐assembly and oil–water–air interfacial self‐assembly successfully enhances the electromagnetic field through plasmonic coupling. In addition, the FDPS substrate retains a high SERS sensitivity after exposure to air at room temperature for 30 days because of the high stability of AuNP arrays and antioxidation characteristic of the PU covered on the aligned AgNWs. Even after undergoing stretching, bending, and twisting for 100 cycles, the FDPS substrate maintains a stable SERS activity owing to the introduction of the elastic PU. This study demonstrates a potential application of SERS detection under practical conditions for irregular surfaces and may be helpful in the development of flexible sensors. Abstract : Through block copolymer self‐assembly and oil–water–air interfacial self‐assembly, an Au‐nanoparticle‐array/aligned‐Ag‐nanowire‐based flexible dual plasmonic surface‐enhanced Raman scattering (SERS, FDPS) substrate is fabricated, which exhibits high SERS sensitivity and reproducibility. The obtained FDPS substrate maintains a stable SERS response after exposure to air at room temperature for 30 days and stretching, bending, and twisting for 100 cycles.